A Review of Current Management of Placental Site Trophoblastic Tumor and Epithelioid Trophoblastic Tumor. Issue 2 (February 2022) - Burkett, Wesley C.; Soper, John T.
Abstract : Importance: Placental site trophoblastic tumor (PSTT) and epithelioid trophoblastic tumor (ETT) are rare forms of gestational trophoblastic neoplasia (GTN). These tumors differ from choriocarcinoma as they are monophasic, have slower growth rates, have lower β-hCG concentrations, and are more chemoresistant. Placental site trophoblastic tumor and ETT can be misdiagnosed, leading to inappropriate management. Objective: The aim of this study was to review the pathogenesis, presentation, pathologic findings, and treatment for PSTT and ETT. Evidence Acquisition: A comprehensive literature review was performed identifying relevant research and review articles. Relevant textbook chapters and guidelines were also reviewed. Results: Placental site trophoblastic tumor and ETT can present months to years after any antecedent pregnancy event with abnormal uterine bleeding and an elevated β-hCG. Tumors are typically confined to the uterus and secrete lower levels of β-hCG compared with other GTNs. The International Federation of Gynecology and Obstetrics prognostic scoring system does not correlate well with prognosis. These lesions can be misdiagnosed as smooth muscle tumors, metastatic melanoma, and cervical squamous cell carcinoma. However, they can be distinguished by their unique histologic and immunophenotypic features. Conclusions: Surgery is the mainstay of treatment for early-stage PSTT and ETT. For patients with advanced disease or for those with poor prognostic indicators, such as an antecedent pregnancy interval of greater than 48 months, a multimodal treatment paradigm of surgery and chemotherapy using a high-risk GTN platinum-etoposide containing regimen is recommended. Relevance: Placental site trophoblastic tumor and ETT should be considered in the differential diagnosis in a reproductive age patient presenting with abnormal uterine bleeding and an elevated β-hCG after any antecedent pregnancy event. Target Audience: Obstetricians and gynecologists, family physicians Learning Objectives: After participating in this activity, the reader should be better able to identify the presentation and diagnosis of PSTT and ETT; explain how PSTT and ETT differ from the more common forms of GTN; and describe how surgical resection is the primary treatment modality for PSTT and ETT.